Kaempferol as a multifaceted immunomodulator: implications for inflammation, autoimmunity, and cancer - Dong, Han; Song, Ge; Wang, Zhe; Wu, Xue; Wang, Qi; Wang, Yue-Hui (Frontiers in Immunology, 2025)
Kaempferol (KMF) is a dietary flavonoid exhibiting profound immunomodulatory effects across multiple immune cell populations. This review synthesizes current insights into how KMF regulates diverse immune cell populations and its therapeutic potential in inflammatory and immune-related disorders. KMF exhibits multifaceted effects on T cells. It inhibits T cell activation via suppressing various signaling pathways and calcineurin. Additionally, it regulates T cell subset balance through the modulation of different transcription factors. In natural killer (NK) cells, KMF enhances proliferation and cytotoxicity. This effect is partly mediated by gut microbiota modulation, which further boosts anti-tumor immunity. For dendritic cells (DCs), KMF shows context-dependent effects. It can promote adaptive immunity in some settings, while in inflammatory contexts, it suppresses DC maturation and cytokine secretion. KMF reduces neutrophil infiltration and the formation of neutrophil extracellular traps (NETs). It also alleviates eosinophil-driven allergic inflammation and blocks mast cell degranulation. Regarding macrophages, KMF shifts polarization from pro-inflammatory M1 to anti-inflammatory M2 phenotypes in metabolic and fibrotic models. In cancer, however, it inhibits the polarization of tumor-associated M2 macrophages. Overall, KMF modulates multiple immune cell types and signaling pathways, positioning it as a promising candidate for treating autoimmune, inflammatory, and neoplastic diseases. Further translational research is warranted to explore its clinical utility and optimize delivery strategies.